The Influence of Operating Revenues and Operating Costs on Net Income of Pharmaceutical Companies Listed on the Indonesia Stock Exchange - Aldi Amartya Saputra; M. Ikhwan Maulana Haeruddin; Nurman Nurman (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of operating income and operating costs on net profit in pharmaceutical companies listed on the Indonesia Stock Exchange. The independent variables in this study are operating income and operating expenses, while the dependent variable is net profit. The population in this study is the financial statements of pharmaceutical sector manufacturing companies that have been listed on the Indonesia Stock Exchange for 2018-2021 of 10 companies. The data analysis technique used is multiple linear regression analysis using SPSS 25.00 for windows. From the test results of multiple linear regression analysis, the following formula can be obtained: Y = Y = -0.845+ 0.425x1 + 0.582x2 + e. Meanwhile, the coefficient of determination = 0.933 means that the operating income and operational costs variables have an effect of 93.3% on net income. While the rest is influenced by other variables not examined in this study.Partial test results for X1 obtained Tcount > Ttable (2,847 > 2.052) with a significance of 0.007 then H1 is accepted and H0 is rejected. Partial test results for X2 obtained Tcount > Ttable (3,833 > 2.052) with a significance of 0.000, H2 is accepted and H0 is rejected. the value of operational costs, the profit earned will be smaller and vice versa if operational costs can be minimized, the profit generated will also be maximized.